A histone deacetylase inhibitor enhances expression of genes inhibiting Wnt pathway and augments activity of DNA demethylation reagent against nonsmall‐cell lung cancer. Issue 10 (14th March 2017) - Shieh, Jiunn‐Min; Tang, Yen‐An; Hu, Fu‐Han; Huang, Wei‐Jan; Wang, Ying‐Jan; Jen, Jayu; Liao, Sheng‐You; Lu, Ying‐Hung; Yeh, Ya‐Ling; Wang, Tseng‐Wei; Lin, Pinpin; Wang, Yi‐Ching
Abstract : Development of new inhibitors targeting histone deacetylases (HDACs) with improved efficacy for solid tumor therapy is urgently needed. Here, we report the development of a novel HDAC inhibitor TMU‐35435 and verify it as a single agent and in combination treatment with DNA demethylation reagent 5‐aza‐2′‐deoxycytidine (5‐aza‐dC) in lung cancer preclinical models. TMU‐35435 exerted cancer‐specific cytotoxicity via mitochondria‐mediated apoptosis. Expression microarrays revealed a unique TMU‐35435‐induced gene networks enriched in biological processes, including "negative regulation of cell proliferation" and "Wnt receptor signaling pathway" compared to FDA‐approved HDAC inhibitor SAHA. TMU‐35435 inhibited tumor growth with good pharmacokinetic properties and safety features in lung orthotopic and subcutaneously implanted xenograft models. TMU‐35435 and 5‐aza‐dC showed synergistic antitumor effects through reactivation of tumor suppressor genes and those genes encoding negative regulators of Wnt signaling pathway in vitro and in vivo . Some genes showed additive inhibition of DNA methylation upon TMU‐35435 and 5‐aza‐dC combined treatment. Our findings suggested that TMU‐35435 is a potential HDAC inhibitor for lung cancer treatment as a single agent and in combination with 5‐aza‐dC. Abstract : What's new? Histone deacetylases (HDACs) fill a critical role in the epigenetic regulation of gene expression. In cancer, however, their over activity contributes to aberrant gene expression and tumor growth. HDAC inhibition is therefore an appealing therapeutic avenue. Here, a novel HDAC inhibitor, TMU‐35435, when administered as a single agent in preclinical lung cancer models, effectively inhibited tumor growth. Given together with a DNA demethylation reagent, TMU‐35435 acted synergistically to induce cell death via reduced DNA methylation and reactivation of tumor suppressor genes that encode negative Wnt signaling regulators. Safety profiles in mice further highlight the potential of TMU‐35435 as a cancer therapy.